Who Teaches the Teachers? A RCT of Peer-to-Peer Observation and Feedback in 181 Schools - Richard Murphy; Felix Weinhardt; Gill Wyness (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper evaluates a widely used, low stakes, teacher peer-to-peer observation and feedback program under Randomized Control Trial (RCT) conditions. Half of 181 volunteer primary schools in England were randomly selected to participate in a two-year program in which three fourth and fifth grade teachers observed each other. We find that two cohorts of students taught by treated teachers perform no better on externally graded national tests compared to business as usual. However this masks large heterogeneity; in small schools, which would have no choice over which teachers would be involved, we find negative impacts of the training (0.1-0.18SD), whereas we find positive impacts in larger schools (0.06-0.17SD). We conclude that the widely-used feedback program that we study is only productive in larger schools, and that centralised one-size-fits-fall teacher training interventions may be harmful.
Keywords: I21; I28; M53; 330; education; teachers; RCT; peer mentoring